Feasibility of Using the Brazilian Version of the GloboDiet Software to Collect Dietary Intake Data - Gustavo Rosa Gentil Andrade; Leandro Teixeira Cacau; Eduardo De Carli; Paulo Andrade Lotufo; Isabela Martins Benseñor; Dirce Maria Marchioni (Dietetics, 2023)
Technological advances, such as the GloboDiet software, have enabled the development of instruments to standardize dietary data collection through the 24-h dietary recall (24HR). Thus, the aim of this study was to evaluate the feasibility of using the Brazilian version of the GloboDiet software. The 24HR method guided by the GloboDiet software was applied by face-to-face (n = 2093) interviews and a second measurement by telephone (n = 1084) interviews with participants from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). The adherence rate was calculated using data from control worksheets filled out by interviewers, whereas the Chi-square test was used to assess differences between sociodemographic groups and the participants’ final adherence status. For the interview’s duration, the data were presented as the median and the interquartile range—IQR (Q1–Q3 (25–75%)). Non-parametric tests were used to assess differences among individuals in terms of the total duration and stages of the interview. Adherence rates were 82.8% face-to-face and 68.4% telephone interviews. The total duration of the face-to-face and telephone interviews was 30.7 (IQR, 23.3–40.7) and 35.3 (IQR, 25.3–49.7) minutes (p < 0.001). These results evidence that the GloboDiet software is viable for the routine of an epidemiological study.